(untitled) (Bangladesh Journal of Agricultural Research, 2012)
An experiment was carried out hydroponically to investigate the arsenic (As) toxicity in rice (Oryza sativa L. cv. Akitakomachi) seedlings in presence of Fe3+-EDTA. The As treatments (NaAsO2) were 0, 6.7, 13.4, 26.8, and 33.5 ?M for 14 days. The whitish chlorotic symptom was pronounced in the fully expanded young leaves at 13.4 ?M As treatment, suggesting that As-induced chlorosis might be Fe (iron)-chlorosis. Chlorophyll indices and Fe concentrations were reduced much in the shoots of As-treated chlorotic seedlings as compared to the control seedlings. Our result showed that Astoxicity largely depended on the concentrations of inorganic As in the medium and the higher was the concentration of As the higher was the As-toxicity. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11742 Bangladesh J. Agril. Res. 36(4): 553-562, December 2011